The Reconstruction of The Concept of Ukhuwah in The Qur’an: A Thematic Tafsir Analysis and Its Relevance in Multicultural Societies - Yasir Arafat; Hasyim Haddade; Rosmini Rosmini (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to examine and reconstruct the concept of ukhuwah (brotherhood) in the Qur’an as a foundation for building harmonious social life within a multicultural society. The background of this research lies in the gap between the ideal values of brotherhood in the Qur’an and the contemporary social reality, which is still marked by conflict, intolerance, and social polarization. This research employs a qualitative approach based on library research, using a thematic exegesis (tafsir maudhu’i) method by collecting and analyzing Qur’anic verses related to the concept of ukhuwah comprehensively. The findings reveal that ukhuwah in the Qur’an has an integrative meaning encompassing theological, social, and humanitarian dimensions, manifested in three main forms: ukhuwwah Islamiyah (Islamic brotherhood), ukhuwwah insaniyah (universal human brotherhood), and ukhuwwah wathaniyah (national brotherhood). Linguistically, the use of various terms such as ikhwah, ikhwan, and akhuhum reflects the depth of brotherhood, including emotional bonds, collective solidarity, and moral responsibility. Furthermore, core values such as rahmah (compassion), wahdah (unity), and ta‘awun (mutual cooperation) serve as the foundation for fostering inclusive and civilized social relations. In the context of a multicultural society, the concept of ukhuwah holds significant relevance as an instrument for promoting social harmony, preventing conflict, and strengthening solidarity across differences. Therefore, reconstructing the concept of ukhuwah in a contextual manner is essential so that it functions not only as a normative doctrine but also as a practical solution to contemporary social challenges.